Credit quality and guarantees: How to interpret the Central Credit Register for a better access to credit1. (July 2017) - Gai, Lorenzo; Ielasi, Federica
Abstract: External guarantees on loans represent an important tool for mitigating the loss given default for a bank, but they are able to produce a negative effect on the firm's probability of default, affecting the overall level of credit risk. The Central Credit Register plays a leading role in determining the rating assigned by banks to firms, typically small and medium enterprises. Firm‐level defaulted and in bonis positions, as well as guaranteed and unsecured loans, are compared using 63, 377 reports from the Italian Central Credit Register for a period of 36 months, from 2012 to 2015. External guarantees are able to affect the credit quality of loans to small businesses.